1998
DOI: 10.1128/aem.64.6.2133-2140.1998
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pyruvate Decarboxylase Overproduction on Flux Distribution at the Pyruvate Branch Point in Saccharomyces cerevisiae

Abstract: A multicopy plasmid carrying the PDC1 gene (encoding pyruvate decarboxylase; Pdc) was introduced in Saccharomyces cerevisiae CEN.PK113-5D. The physiology of the resulting prototrophic strain was compared with that of the isogenic prototrophic strain CEN.PK113-7D and an empty-vector reference strain. In glucose-grown shake-flask cultures, the introduction of thePDC1 plasmid caused a threefold increase in the Pdc level. In aerobic glucose-limited chemostat cultures growing at a dilution rate of 0.10 h−1, Pdc lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 48 publications
(65 reference statements)
4
30
0
1
Order By: Relevance
“…The onset of aerobic fermentation in yeast can be, at least in part, attributed to glucose repression. In the case of S. cerevisiae CEN.PK113-7D, two observations are in accordance with this hypothesis: the fact that the speci¢c oxygen uptake rate decreases above the critical dilution rate [29] and the fact that an increase in the critical dilution rate of this strain can be achieved via the manipulation of genes involved in glucose repression/derepression: deletion of MIG1 and MIG2 [30] and overexpression of HAP4 [31]. In light of this, a likely explanation for the lower critical dilution rates of the recombinant strains observed in the current work can be that, as the need for NADPH production is decreased by the genetic manipulations, and a relatively larger fraction of the glucose is £owing through the Embden^Meyerhof^Parnas (EMP) pathway, the increased £ux through this pathway leads to the onset of glucose repression at lower speci¢c glucose uptake rates.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The onset of aerobic fermentation in yeast can be, at least in part, attributed to glucose repression. In the case of S. cerevisiae CEN.PK113-7D, two observations are in accordance with this hypothesis: the fact that the speci¢c oxygen uptake rate decreases above the critical dilution rate [29] and the fact that an increase in the critical dilution rate of this strain can be achieved via the manipulation of genes involved in glucose repression/derepression: deletion of MIG1 and MIG2 [30] and overexpression of HAP4 [31]. In light of this, a likely explanation for the lower critical dilution rates of the recombinant strains observed in the current work can be that, as the need for NADPH production is decreased by the genetic manipulations, and a relatively larger fraction of the glucose is £owing through the Embden^Meyerhof^Parnas (EMP) pathway, the increased £ux through this pathway leads to the onset of glucose repression at lower speci¢c glucose uptake rates.…”
Section: Discussionsupporting
confidence: 58%
“…However, lower values are found in the literature for the critical dilution rate of S. cerevisiae CEN.PK113-7D. In particular, the usage of chemostat cultivations indicates a critical dilution rate for this strain of around 0.3 h 31 [29]. These di¡erences are almost certainly due to varying ethanol detection limits for the di¡erent set-ups: the concentration of ethanol in the fermenter at the critical dilution rate can be estimated from the plots presented in the work of [29] to be 5.8 mg l 31 , in contrast to 30^60 mg l 31 in the current work.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Glycerol and organic acids were determined by HPLC [16]. Glucose in reservoir media and supernatants was determined enzymically using a commercial glucose oxidase kit (Merck systems 14144).…”
Section: Metabolite Analysismentioning
confidence: 99%
“…However, this redistribution of £uxes only a¡ected the mode of fermentative metabolism, and not the relative contribution of respiration and fermentation to sugar dissimilation. It has recently been demonstrated that a 5^10-fold overexpression of pyruvate decarboxylase in S. cerevisiae led to a decrease of the dilution rate at which aerobic fermentation set in during aerobic, glucose-limited chemostat cultures [17], and thus a¡ected the balance between respiration and fermentation. Apparently, the high pyruvate decarboxylase levels in the overexpressing strain competed for pyruvate with the enzymes involved in mitochondrial oxidation of pyruvate.…”
Section: Discussionmentioning
confidence: 99%